학동기 아동에서 Dream Lens(TM) 의 유효성 및 안정성 평가 - 위호영; Ho Young Wie; 이담호; Dam Ho Lee; 김준모; Joon Mo Kim (Daihan angwa haghoi jabji, 2004)
목적 : 학동기 아동에서 제 3세대 역기하렌즈인 드림렌즈(OK B+ series lenses, Contex, USA)의 근시교정 효과 및 안전성을 알아보고자 하였다. 대상과 방법 : 2002년 9월부터 2003년 3월 사이에 비전안과에서 드림렌즈 처방을 받은 후 3개월 이상 추적 관찰된 7세부터 13세 사이의 환아 23명 45안을 대상으로 세극등검사, 나안시력, 자동굴절검사 및 각막곡률측정, 각막지형도검사를 착용 전 그리고 착용 후 일주, 1개월, 3개월 째 시행하여 근시교정효과와 합병증 발생 여부를 알아보았다. 결과 : 렌즈 착용 전 평균 구면렌즈대응치는 -2.54±1.00 디옵터(범위: -0.63∼-4.00)였으며 렌즈 착용 전 나안시력 0.5 이상은 11.1% 이였고 0.8 이상은 없었다. 렌즈 착용 1주 후 나안시력이 0.8 이상인 경우가 80%이였으며, 착용 1개월, 3개월 후에는 각각 78% 와 91%이었고 착용 1주까지 가장 급격한 시력향상을 보였다. 3개월 추적관찰기간동안 45명 중 4안에서 표층점상각막염이 발생하였으나 렌즈를 착용할 수 없을 정도의 각막상피손상이나 다른 합병증은 발생하지 않았다. 결론 : 드림렌즈는 중등도 이하의 근시를 가진 학동기 아동에 있어 일시적으로 굴절이상을 교정하여 나안시력을 향상시키는 효과적인 방법 중의 하나이다. 눈 건강에 미치는 장기 영향에 관해서는 추가 연구가 필요하리라 생각된다. <한안지 45(6):913-919, 2004> Purpose: This project was designed to study the effectiveness and safety of Dream lensTM (OK B+ series lenses, Contex, USA) in correcting myopia in a population of school children, under 13 years old. Methods: Twenty-three school children aged 7 to 13 years followed over a 3-month period were fitted with lenses in the Vision Eye Center from September 2002 to March 2003. Slit lamp examination, uncorrected visual acuity, autorefraction and autokeratometry by Canon RK-5 and topography were measured at baseline and at 1week, 1 month, and 3 months after the lenses were worn. Results: The mean baseline autorefraction was -2.54±1.00 diopters (range: -0.63∼-4.00) and baseline uncorrected visual acuity over 0.5 was 11.1% and over 0.8 was 0%. Vision correction of over 0.8 was found in 80% of the cases in the first 1 week, 78% at 1 month, 91% at 3 months with the most rapid improvement occurring during the first 1 week. Superficial punctate keratitis occurred in 4 of 45 eyes, but there was no other pathologic problem. Conclusions: Dream lens is an effective and safe means of temporarily reducing myopia in a certain range of myopic patients; however, further studies are needed to determine the long-term effects on the eye health. J Korean Ophthalmol Soc 45(6):913-919, 2004